2020
DOI: 10.1016/j.ssresearch.2019.102387
|View full text |Cite
|
Sign up to set email alerts
|

The social and genetic inheritance of educational attainment: Genes, parental education, and educational expansion

Abstract: Recently, several genome-wide association studies of educational attainment have found education-related genetic variants and enabled the integration of human inheritance into social research. This study incorporates the newest education polygenic score (Lee et al. 2018) into sociological research, and tests three gene-environment interaction hypotheses on status attainment. Using the Health and Retirement Study (N = 7,625), I report three findings. First, a standard deviation increase in the education polygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Another study showed that school performance increased in youth when parental education was improved ( 44 ). Sociologists also found that wealthier families were frequently better able to provide offspring with superior resources, and these, in turn, assure their academic success ( 45 ). Therefore, through providing additional financial support to children with lower family economic incomes and encouraging parents to continue learning, management of those areas early on may assist in improving their adult functioning, including educational attainment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that school performance increased in youth when parental education was improved ( 44 ). Sociologists also found that wealthier families were frequently better able to provide offspring with superior resources, and these, in turn, assure their academic success ( 45 ). Therefore, through providing additional financial support to children with lower family economic incomes and encouraging parents to continue learning, management of those areas early on may assist in improving their adult functioning, including educational attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, through providing additional financial support to children with lower family economic incomes and encouraging parents to continue learning, management of those areas early on may assist in improving their adult functioning, including educational attainment. The mechanism underlying this intergenerational transmission of educational attainment requires further exploration but includes genetic influences and gene–environment interaction effects ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on the Scarr-Rowe hypothesis has mainly focused on cognitive ability (e.g., Figlio et al, 2017;Guo and Stearns, 2002;Turkheimer et al, 2003;Gottschling et al 2017), although recent studies shifted the focus to education (e.g., Baier and Lang 2019;Conley et al 2015:201;Domingue et al 2015;Erola et al 2021;Lin 2020). Nearly all studies on the Scarr-Rowe hypothesis used some indicator of parents' social standing to capture differences in the quality of the rearing environment.…”
Section: Previous Researchmentioning
confidence: 99%
“…A recent study for Norway does not report any systematic variation in education PGS by parental social background (Isunget et al 2021), while findings for the United States remain mixed (Conley et al 2015;Domingue et al 2015). A recent study by Lin (2020) used the most recent, and therefore more predictive educational PGS (Lee et al 2018), and found that the importance of genes tends to decrease by parents' education.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation